OPTIMALISASI PEMBELAJARAN MELALUI PENYUSUNAN MODUL (DIGITAL BOOK) PADA MATA KULIAH STATISTIKA PENDIDIKAN DI PRODI PENDIDIKAN GURU SEKOLAH DASAR UNIVERSITAS CENDERAWASIH - Maya Pujowati; Tri Suwarningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to enhance the effectiveness of teaching descriptive and inferential statistics to third-semester students of the Primary School Teacher Education (PGSD) Program at Universitas Cenderawasih through the development of an interactive digital learning module based on constructivist theory. The module is equipped with instructional videos, interactive simulations, online quizzes, and discussion forums to facilitate both independent and collaborative learning. The research results show a significant increase (p<0.05) in learning motivation by 25% and conceptual understanding of statistics by 15% in the experimental group using the digital module compared to the control group. Qualitative analysis revealed that students felt more motivated, actively engaged, and able to connect statistical concepts with real-world situations. This digital module demonstrates great potential as a more engaging and effective alternative learning resource, particularly in the context of online or blended learning.